A review on association of Karnanada and diabetes mellitus - Bishnoi, Rakesh; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2020)
Tinnitus is the perception of ringing sound and noise in the ear which is originated within the patient. Diabetes mellitus (DM) is a group of metabolic diseases in which there are high blood sugar levels over a prolonged period. Tinnitus is also a side-effect of some metabolic disorders, medications, and may also result from an abnormally high level of insulin. Acharya Sushruta says when Vata covered with Doshas taking faulty passage get located in sound carrying channels, then the patient perceives various types of sound; this disease is known as Pranada or Karnanada. In this conceptual paper an attempt is made to find out a association between diabetic and tinnitus on the basis of Ayurvedic prospective. This conceptual study has compiled from ancient Samhitas, previous thesis, and different books and published articles. Hyperglycemic condition may damage the 8thcranial nerve, which is the nerve responsible for sound transmission and balance maintenance from the inner ear to the brain. Also the raised blood sugar level can disturb the normal physiology of sodium-potassium ATPase pump, which is responsible for creating the pathogenesis of tinnitus. Therefore, tinnitus can be taken as a complication of diabetes mellitus.